2013
DOI: 10.2169/internalmedicine.52.8786
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Eye Movement Sleep Behavior Disorder in a Patient with Brainstem Lymphoma

Abstract: Rapid eye movement (REM) sleep behavior disorder (RBD) is common in patients with neurodegenerative diseases. RBD occurring in a patient with brainstem lymphoma has not yet been reported. A 30-year-old man had an eleven-month history of violent motor and vocal behavior during sleep. Brain magnetic resonance imaging disclosed hypointensity T1 and hyperintensity T2 signals in the pontomesencephalic junction and at the upper/mid pons level. A stereotactic biopsy demonstrated the presence of diffuse large B-cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Other examples of secondary RBD include those caused by neurological lesion affecting sleep/wake regulatory brain regions, most commonly within the brainstem. RBD due to lesions is rare and most commonly associated with meningiomas and subsequent disruption of pontine REM-atonia structures ( 23 ), although cases of narcolepsy ( 24 ), pontine cavernoma ( 25 ), pontine lymphoma ( 26 ), multiple sclerosis ( 27 ), and acute inflammatory rhombencephalitis ( 28 ) all give further examples of RBD incidence secondary to lesion.…”
Section: Symptoms and Diagnostic Considerationsmentioning
confidence: 99%
“…Other examples of secondary RBD include those caused by neurological lesion affecting sleep/wake regulatory brain regions, most commonly within the brainstem. RBD due to lesions is rare and most commonly associated with meningiomas and subsequent disruption of pontine REM-atonia structures ( 23 ), although cases of narcolepsy ( 24 ), pontine cavernoma ( 25 ), pontine lymphoma ( 26 ), multiple sclerosis ( 27 ), and acute inflammatory rhombencephalitis ( 28 ) all give further examples of RBD incidence secondary to lesion.…”
Section: Symptoms and Diagnostic Considerationsmentioning
confidence: 99%
“…Rapid eye movement sleep behavior disorder (RBD) is frequent in patients with neurodegenerative diseases. RBD was associated with the risk of developing brainstem lymphoma 22 . Above evidence indicated that cancer frequently occurs in many individuals with parasomnias.…”
Section: Introductionmentioning
confidence: 95%
“…Focal lesions of the pontine tegmentum region, such as stroke, demyelination and malignancy have been associated with RBD. 2,[12][13][14] Volumetric studies in patients with RBD in PD have also suggested a strong role of this specific area in the pathogenesis of RBD, with smaller volumes in the pontomesencephalic tegmentum, as well as the medullary reticular formation, hypothalamus, thalamus, putamen, amygdala, and anterior cingulate cortex. 15 In our case, immunostaining for tau revealed neuronal loss and tau-positive inclusions exactly in the principle areas of interest in the pontomesencephalic tegmentum.…”
Section: Discussionmentioning
confidence: 99%